Universal size effect studies using three point beam tests - Şener, S.; Şener, K.C. (ISEC Press, 2016)
The universal size effect law for concrete is a law that describes the dependence of nominal strength of specimen or structure on both its size and the crack (or notch) length, over the entire of interest, and exhibits the correct small and large size asymptotic properties as required. The main difficulty has been the transition of crack length from 0, in which case the size effect mode is Type 1, to deep cracks (or notches), in which case the size effect mode is Type 2 and fundamentally different from Type 1. The current study is based on recently obtained comprehensive fracture test data from three-point bending beams tested under identical conditions. This paper presents a studying to improve the existing universal size effect law using the experimentally obtained beam strengths for various different specimen sizes and all notch depths. The updated universal size effect law is shown to fit the comprehensive data quite well. © 2016 ISEC Press.
1st European-Mediterranean Conference on Structural Engineering and Construction, EURO-MED-SEC-1 2016 -- 24 May 2016 through 29 May 2016 -- -- 259929
Keywords: Concrete Fracture; Flexural Strength; Fracture Testing; Notch Depth Effect; Quasi-Brittle Fracture; Scaling Of Strength; Statistical Testing